ANALISIS KINERJA KEUANGAN SEBELUM DAN SESUDAH AKUISISI - Mery Wahyu Rahmadhani; Siti Sundari (Jurnal Ilmiah Akuntansi Peradaban, 2022)
This study aims to test and prove the existence of differences in the company's financial performance before and after the acquisition of service companies listed on the Indonesia Stock Exchange (IDX). The population of this study are service companies listed on the Indonesia Stock Exchange and made acquisitions in 2014 amounted to 13 companies, with purposive sampling method obtained a sample of 5 companies. This study uses secondary data in the form of financial performance for 11 years, starting in 2009 – 2019. Financial performance is proxied by Return on Assets, Net Profit Margin, Earnings per Share. Current Ratio, and Debt to Equity Ratio. The analytical method used is the paired sample t-test with SPSS 25 software. The results showed a significant difference in Earnings per Share and Debt to Equity Ratio before and after the acquisition, but Return on Assets, Net Profit Margin and Current Ratio, did not show the difference before and after the acquisition.